Two new species of the ground beetle subgenus Sadonebria Ledoux & Roux, 2005 (Coleoptera, Carabidae, Nebria) from Japan and first description of larvae of the subgenus - Sasakawa, Kôji (Zookeys, 2016)
Abstract. Sadonebria Ledoux & Roux, 2005 is one of the more diverse subgenera of the genus Nebria Latreille, 1802 in East Asia, and its taxonomy remains unrevised at the subgeneric and specific levels. In this paper, two new species of this subgenus are described from Japan. Nebria quinquelobata sp. n. is described from Mt. Myôkô and is externally similar to Nebria saeviens Bates, 1883, to which specimens of this new species previously had been assigned. Nebria yatsugatakensis sp. n. is described from the Yatsugatake Mountains and is externally similar to locally adjacent species that had been recognized as Nebria sadona Bates, 1883 and were recently revealed as separate species. Both new species are distinguished by morphological (the shape of the endophallus) and morphometric (geometric morphometrics of the pronotum and aedeagus) features. For Nebria yatsugatakensis, the morphology of all larval instars is described based on specimens reared from eggs laid by collected adults. These results, together with previous studies of the species-level taxonomy of Sadonebria and larval morphology of other Nebria subgenera, suggest (i) the utility of geometric morphometrics in species-level taxonomy; (ii) the importance of larval secondary setae in the subgeneric taxonomy of the genus Nebria; and (iii) the presence of further cryptic species in Sadonebria.